2008
DOI: 10.1021/es7031955
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Stability of Mercury and Methylmercury in a Varved Lake Sediment Deposit

Abstract: Using lake sediments to infer past total mercury and methylmercury loading to the environment requires that diagenetic processes within the sediment do not significantly affect the concentrations or net accumulation rates of the mercury species. Because carbon is lost during early sediment diagenesis, the close link between carbon and mercury raises the question of how reliable lake sediments are as archives of total mercury and methylmercury loading. In this study we used a series of freeze cores taken in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 43 publications
(66 reference statements)
1
34
0
Order By: Relevance
“…Consequently, these increases cannot be explained by a rapid influx of catchment material or enhanced Hg scavenging by organic matter. Moreover, lake sediment burdens of total Hg are largely unaffected by diagenetic processes (12,13), and represent minimum estimates of total Hg deposited to a lake surface because of reductive losses before final burial (14). Because we know of no natural mechanism capable of replicating such large and synchronized increases in Hg deposition in 2 adjacent lakes, and given their proximity to a major cinnabar deposit, we attribute with confidence the early increases of Hg observed at LY1 and LY2 to the emergence of regional-scale cinnabar mining at Huancavelica.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, these increases cannot be explained by a rapid influx of catchment material or enhanced Hg scavenging by organic matter. Moreover, lake sediment burdens of total Hg are largely unaffected by diagenetic processes (12,13), and represent minimum estimates of total Hg deposited to a lake surface because of reductive losses before final burial (14). Because we know of no natural mechanism capable of replicating such large and synchronized increases in Hg deposition in 2 adjacent lakes, and given their proximity to a major cinnabar deposit, we attribute with confidence the early increases of Hg observed at LY1 and LY2 to the emergence of regional-scale cinnabar mining at Huancavelica.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work indicated Hg chronologies may be confounded by biological reworking of sediments and sorption of Hg onto redox sensitive metals, such as Fe (Rasmussen 1994). However, Lockhart et al (2000) analyzed Hg in sediment cores from polluted sites and verified sediment total mercury profiles were stable over time, while Rydberg et al (2008) reported diagenesis did not significantly obfuscate Hg trends in sediment cores over a 30-year period. In core BBL-1, there was a lack of correlation between Fe and Hg levels (r 2 = 0.00, p [ 0.95, n = 8), while there was a strong correlation between Al and Fe levels (r 2 = 0.88, p \ 0.01, n = 17), suggesting a low probability that diagenetic remobilization impacted Hg levels.…”
Section: Diagenetic Remobilizationmentioning
confidence: 95%
“…7 and their average sediment accumulation rate value of 0.013 g cm À2 year À1 , a demethylation rate constant of 4 Â 10 À5 d À1 can be calculated. Rydberg et al (2008) also reported a decline in {MeHg} with sediment age in the varved sediments of Lake Nylandssjö n; using the data shown in their Fig. 3a, we calculate a demethylation rate constant of 6 Â 10 À5 d À1 .…”
Section: Modeling the [Mehg] Profilesmentioning
confidence: 82%
“…Surface sediments are enriched in {MeHg} in Basin A, but not in Basin B. Surface sediment enrichments in MeHg were also observed in other lake sediments and were attributed to MeHg production and/or deposition at the sediment surface and subsequent demethylation with sediment burial (Hines et al, 2004;He et al, 2007;Rydberg et al, 2008). In the Fe-rich deposits collected with the Teflon sheets in Basin A, the average (n = 7) {MeHg}:{Fe} molar ratio was 6.5 ± 1.9 Â 10 À10 , a much lower value than that found in the top 0.5-cm sediment layer (4.9 Â 10 À8 ; Table 3).…”
Section: Solid-phasementioning
confidence: 94%
See 1 more Smart Citation